A rare case of non-specific chronic supraglottic laryngitis in a young female: a comprehensive case report - Dandala, Sridhar Reddy; Gonuru, Vinod Kumar; Chilukuri, Ramya Sudha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Chronic non-specific supraglottic laryngitis is a rare clinical condition characterized by chronic inflammation of the supraglottic structures without any evidence of infection, granulomatous disease, autoimmunity or malignancy. This is a case report of a young female presenting with a long-standing history of voice change and dysphagia. Laryngoscopy revealed diffuse inflammation of the supraglottis. Thorough workup, including radiological investigations, blood tests, bronchoscopy and biopsy, ruled out any known etiology. She was thus diagnosed with non-specific chronic supraglottic laryngitis. The patient responded well to the long-term use of oral corticosteroids and immunosuppressant drugs. This study summarizes the clinical presentation, comprehensive investigations and management of chronic, non-specific supraglottic laryngitis.